N-type TOPCon battery front grid line silver-aluminum paste and battery
By using modified aluminum powder and organic modifiers in the front gate wire silver aluminum paste of N-type TOPCon battery, the problem of gate breakage and silver aluminum spike caused by aluminum powder agglomeration is solved, and the VOC and contact performance of the battery are improved.
Patent Information
- Application Number
- CN202311154965.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-06
- Publication Date
- 2025-03-11
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
During the printing process, the existing N-type TOPCon battery front grid line silver aluminum paste has problems such as grid breakage and silver aluminum spike due to agglomeration of aluminum powder during the printing process, resulting in PN damage, VOC and reduced efficiency.
Silver aluminum paste composed of modified aluminum powder, silver powder, lead glass powder, silicon glass powder and organic carrier is used. The surface of the modified aluminum powder is covered with organic modifiers to improve its surface oil absorption rate, reduce the interaction between aluminum powder, and improve the compatibility and dispersion of aluminum powder and slurry.
By covering the surface of the modified aluminum powder with organic modifiers, the agglomeration and surface oxidation of the aluminum powder are reduced, the smoothness and sintering efficiency of the silver aluminum paste are improved, the number and size of the silver aluminum spikes are reduced, and the VOC and contact performance of the battery are improved.
Smart Images

Figure CN119601280A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of crystalline silicon solar cell manufacturing, and in particular to an N-type TOPCon cell front grid line silver-aluminum paste and a cell. Background Art
[0002] Currently, N-type TOPCon cells in crystalline silicon solar cells are widely used due to their small attenuation, obvious advantages in overall cell efficiency and power generation.
[0003] The existing N-TOPCon front fine grid paste is silver-aluminum paste, in which aluminum powder is used to form a good aluminum-silicon alloy layer with silicon under certain temperature conditions and form P+ layer doping. However, aluminum doped in the middle of silver powder is prone to agglomeration, and its surface oil absorption rate is large, which causes the paste to agglomerate during the printing process, resulting in broken grids and silver-aluminum spikes, which in turn leads to PN damage, VOC and reduced efficiency. Summary of the invention
[0004] The technical problem to be solved by the present invention is to provide an N-type TOPCon battery front grid line silver-aluminum paste and a battery to solve the problem that the existing N-type TOPCon battery front grid line silver-aluminum paste is prone to grid breakage and silver-aluminum spikes due to aluminum powder agglomeration during the printing process.
[0005] In order to solve the above problems, the present invention is achieved through the following technical solutions:
[0006] The present invention proposes a silver-aluminum paste for the front grid line of an N-type TOPCon battery, wherein the components constituting the silver-aluminum paste include modified aluminum powder, silver powder, lead glass powder, silicon glass powder and an organic carrier, and the modified aluminum powder is aluminum powder with an organic modifier coated on the surface.
[0007] Furthermore, in the silver-aluminum paste, the mass fractions of the modified aluminum powder, silver powder, lead glass powder, silicon glass powder and organic carrier are 1-8%, 70-90%, 1-10%, 0.1-3% and 5-15%, respectively.
[0008] Furthermore, in the silver-aluminum paste, the organic modifier is one or more of stearic acid, silane coupling agent, oleic acid, and fatty acid.
[0009] Furthermore, in the silver aluminum paste, the modified aluminum powder is micron spherical aluminum powder, and / or
[0010] The D50 of the modified aluminum powder is 1 to 4 microns.
[0011] Furthermore, in the silver-aluminum paste, the silver powder is micron-spherical silver powder, and / or
[0012] The D50 of the silver powder is 0.5 to 3 microns.
[0013] Furthermore, in the silver aluminum paste, the lead glass powder is a lead-boron-zinc system glass powder, and / or
[0014] The silicon glass powder is silicon-boron-zinc-calcium system glass powder.
[0015] Furthermore, in the silver-aluminum paste, the organic carrier includes 4 to 6 parts of organic polymer resin, 93 to 95 parts of organic solvent and 0.5 to 2 parts of organic additives by weight.
[0016] Furthermore, in the silver aluminum paste, the organic polymer resin includes one or more of EC and acrylic acid, and / or
[0017] The organic solvent includes one or more of butyl carbitol, terpineol, tributyl citrate, and / or
[0018] The organic additive is polyamide wax.
[0019] Furthermore, in the silver-aluminum paste, the silicon glass powder includes 5-20% by mass of calcium oxide, 10-60% by mass of boron oxide, 5-15% by mass of zinc oxide, and 10-30% by mass of silicon oxide.
[0020] The present invention further provides an N-type TOPCon battery, wherein a plurality of grid lines are attached to the front side of the N-type TOPCon battery, and the grid lines are prepared from the above-mentioned silver-aluminum paste.
[0021] Compared with the prior art, the embodiments of the present invention have the following advantages:
[0022] In the embodiment of the present invention, the silver-aluminum paste for the front grid line of the N-type TOPCon battery provided comprises modified aluminum powder, silver powder, lead glass powder, silicon glass powder and organic carrier, and the modified aluminum powder is aluminum powder coated with an organic modifier on the surface. Among them, by coating the surface of the aluminum powder with an organic modifier to improve its surface oil absorption rate, not only the interaction between the aluminum powders is reduced, but also the aluminum powder and the organic carrier in the slurry have better compatibility, and can be quickly and evenly dispersed into the organic or slurry, thereby reducing the agglomeration and fineness of the slurry, and ensuring smooth printing on a thin line width screen; at the same time, the organic coating is on the surface of the aluminum powder to reduce the surface oxidation of the aluminum powder, which is conducive to the flow of aluminum liquid at a lower temperature during the sintering process, improving contact and efficiency, so that the silver-aluminum spikes on the silicon contact surface after sintering are small and numerous, thereby improving the VOC and contact performance of the battery, thereby solving the problem that the silver-aluminum paste for the front grid line of the existing N-type TOPCon battery is prone to broken grids and silver-aluminum spikes due to aluminum powder agglomeration during printing.
[0023] It should be understood that the foregoing general description and the following detailed description are exemplary and explanatory only and are not restrictive of the present application. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 It is a schematic diagram of the structure of modified aluminum powder in the silver aluminum paste of the front grid line of an N-type TOPCon battery provided by an embodiment of the present invention. DETAILED DESCRIPTION
[0025] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the present invention is further described in detail below with reference to the accompanying drawings and specific embodiments.
[0026] The applicant of the present invention has found that the front fine grid paste of the existing N-type TOPCon is silver-aluminum paste, and the solid conductive phase of the paste mainly includes 95-97% silver powder and 3-5% aluminum powder. Among them, although the aluminum powder can form a good aluminum-silicon alloy layer and form a P+ layer doping with silicon under certain temperature conditions, the aluminum doped in the middle of the silver powder is prone to agglomeration, and its surface oil absorption rate is relatively large, so that the paste will cause broken grids and silver-aluminum spikes due to agglomeration during the printing process, which will lead to PN damage, VOC and efficiency reduction. In particular, the grid line width of the existing N-type TOPCon battery is getting narrower and narrower, making the above problems more prominent.
[0027] In order to solve the above problems, the embodiment of the present invention provides a silver-aluminum paste for the front grid line of an N-type TOPCon battery, wherein the components constituting the silver-aluminum paste include modified aluminum powder, silver powder, lead glass powder, silicon glass powder and an organic carrier, wherein Figure 1 As shown, the modified aluminum powder 10 includes a core 11 and an organic modifier 12 coated on the surface of the core 11. The core is aluminum powder, that is, the modified aluminum powder is aluminum powder with the organic modifier coated on the surface.
[0028] Among them, modified aluminum powder and silver powder are the main components; lead glass powder and silicon glass powder are inorganic adhesives, which will melt into liquid under high temperature conditions and condense when cooled to play a bonding role; the organic carrier can ensure the overall bonding effect and reduce the overall viscosity of the slurry; at the same time, because the surface of the modified aluminum powder is coated with an organic modifier, its surface oil absorption rate can be improved, which not only reduces the interaction between aluminum powders, but also makes the aluminum powder and the organic carrier in the slurry have better compatibility, and can be quickly and evenly dispersed into the organic or slurry, thereby reducing the agglomeration and fineness of the slurry, and ensuring smooth printing on a fine line and wide screen; at the same time, the organic is coated on the surface of the aluminum powder to reduce the surface oxidation of the aluminum powder, which is conducive to the flow of aluminum liquid at a lower temperature during the sintering process, improves contact and efficiency, and makes the silver-aluminum spikes on the silicon contact surface after sintering small and large in number, thereby improving the VOC and contact performance of the battery, thereby solving the problem that the silver-aluminum paste of the front grid line of the existing N-type TOPCon battery is prone to broken grids and silver-aluminum spikes due to aluminum powder agglomeration during printing.
[0029] Optionally, in one embodiment, the organic modifier coated on the surface of the aluminum powder may be one or more of stearic acid, silane coupling agent, oleic acid, and fatty acid. Optionally, in some embodiments, the organic modifier coated on the surface of the aluminum powder may be at least two of stearic acid, silane coupling agent, oleic acid, and fatty acid. Among them, using different contents and different types of organic modifiers to coat the surface of the aluminum powder can more effectively improve the surface oil absorption rate of the aluminum powder, which is conducive to forming better compatibility and dispersibility with the organic carrier.
[0030] Optionally, in one embodiment, the modified aluminum powder is micron-spherical aluminum powder, which is more conducive to uniform dispersion in the organic carrier, further reduces agglomeration, and ensures printing smoothness.
[0031] Optionally, in one embodiment, the D50 of the modified aluminum powder is 1 to 4 microns, for example, in the range of 1 micron, 2 microns, 3 microns, 4 microns, or any two of them.
[0032] Wherein, the preparation method of modified aluminum powder is as follows:
[0033] Weigh a certain amount of an organic modifier in a beaker or other container, wherein the organic modifier is one or more of stearic acid, silane coupling agent, oleic acid, and fatty acid;
[0034] Then weigh a fixed amount of solvent butyl carbitol and add it to a beaker, place it in a magnetic stirrer, control the temperature at 60 degrees, stir at a speed of 400-800 rpm for 30 minutes, then cool it, weigh a certain amount of aluminum powder and add it to the cooled beaker, stir at a speed of 300-500 rpm for 4 hours, and finally filter out excess solvent and modifier with filter paper to obtain modified aluminum powder.
[0035] Optionally, in one embodiment, the silver powder is micron spherical silver powder, and its D50 can be 0.5 to 3 microns, for example, 0.5 microns, 1 micron, 1.5 microns, 2 microns, 2.5 microns, 3 microns, or any two of the range values.
[0036] Optionally, in one embodiment, the lead glass powder is a lead-boron-zinc system glass powder, which is used as the main glass component. The components of the lead-boron-zinc system glass powder include but are not limited to main oxide components such as lead oxide, boron oxide, zinc oxide, and contain a small amount of silicon oxide, aluminum oxide, etc. In practical applications, the lead-boron-zinc system glass powder in the prior art can be used.
[0037] Optionally, in one embodiment, the silicon glass powder is a silicon-boron-zinc-calcium system glass powder, which serves as a secondary glass component and includes, but is not limited to, silicon oxide, calcium oxide, boron oxide, zinc oxide, and the like.
[0038] Optionally, in a specific embodiment, the silicon glass powder includes 5-20% by mass of calcium oxide, 10-60% by mass of boron oxide, 5-15% by mass of zinc oxide, and 10-30% by mass of silicon oxide.
[0039] Wherein, the preparation method comprises the following steps:
[0040] (1) weighing the raw materials of various components of the silicon glass powder according to the mass ratio, grinding or mixing with a stirrer, and then drying;
[0041] (2) placing the dried glass powder raw material into a crucible, placing the crucible into a high-temperature furnace for firing, heating to 800-1400° C. and maintaining the temperature for 0.2-6 hours to obtain a silica glass melt; wherein the constant temperature is preferably 900-1200° C., and the constant temperature time is preferably 0.5-3 hours;
[0042] (3) quenching the silicon glass melt with deionized water, removing the glass slag after cooling, and drying it;
[0043] (4) grinding the glass slag using a ball mill to an average particle size of 0.1 to 5 μm;
[0044] (5) Sieve and dry to obtain silica glass powder.
[0045] Optionally, in one embodiment, the organic vehicle comprises, by weight, 4 to 6 parts of an organic polymer resin, 93 to 95 parts of an organic solvent and 0.5 to 2 parts of an organic additive.
[0046] For example, the organic vehicle includes 4 parts of organic polymer resin, 95 parts of organic solvent and 1 part of organic additive by weight.
[0047] For example, the organic vehicle includes 6 parts of organic polymer resin, 93 parts of organic solvent and 1 part of organic additive by weight.
[0048] For example, the organic vehicle includes 4 parts of an organic polymer resin, 94 parts of an organic solvent, and 2 parts of an organic additive, by weight.
[0049] For example, the organic vehicle includes 5 parts of organic polymer resin, 94.5 parts of organic solvent and 0.5 parts of organic additive by weight.
[0050] For example, the organic vehicle includes 5 parts of organic polymer resin, 94 parts of organic solvent and 1 part of organic additive by weight.
[0051] Optionally, in one embodiment, the organic polymer resin includes one or more of EC and acrylic acid. For example, by weight, the organic polymer resin may include 2 parts of EC and 1 part of acrylic acid.
[0052] Optionally, in one embodiment, the organic solvent includes one or more of butyl carbitol, terpineol, and tributyl citrate. For example, by mass, the organic solvent may include 2 parts of butyl carbitol, 1 part of terpineol, and 1 part of tributyl citrate.
[0053] Optionally, in one embodiment, the organic additive is polyamide wax.
[0054] Optionally, in the silver-aluminum paste for the front grid line of the N-type TOPCon battery provided in an embodiment of the present invention, the mass fractions of modified aluminum powder, silver powder, lead glass powder, silicon glass powder and organic carrier are 1-8%, 70-90%, 1-10%, 0.1-3% and 5-15% respectively.
[0055] For example, in the above silver-aluminum paste, the mass fractions of modified aluminum powder, silver powder, lead glass powder, silicon glass powder and organic carrier are 1%, 73.9%, 10%, 0.1% and 15% respectively.
[0056] For example, in the above silver-aluminum paste, the mass fractions of modified aluminum powder, silver powder, lead glass powder, silicon glass powder and organic carrier are 8%, 83%, 1%, 3% and 5% respectively.
[0057] For example, in the above silver-aluminum paste, the mass fractions of modified aluminum powder, silver powder, lead glass powder, silicon glass powder and organic carrier are 8%, 70%, 10%, 0.1% and 11.9% respectively.
[0058] For example, in the above silver-aluminum paste, the mass fractions of modified aluminum powder, silver powder, lead glass powder, silicon glass powder and organic carrier are 2%, 90%, 2%, 1% and 5% respectively.
[0059] For example, the mass fractions of modified aluminum powder, silver powder, lead glass powder, silicon glass powder and organic carrier are 5%, 81.5%, 4%, 0.5% and 9% respectively.
[0060] Optionally, the slurry is prepared as follows:
[0061] (1) 1 to 8 parts of modified aluminum powder, 1 to 10 parts of lead glass powder, 0.1 to 3 parts of silicon glass powder and 3 to 13 parts of organic carrier are mixed by weight, and dispersed at a speed of 200 to 800 rpm for 10 to 60 minutes by a disperser, and then 70 to 90 parts of silver powder are added and dispersed at a speed of 1000 to 2000 rpm by a disperser for 30 to 60 minutes, and then ground on a three-roll grinder for 3 to 8 times.
[0062] (2) After grinding, an organic carrier accounting for 0.1 to 2% of the total raw material is added, and a high-speed disperser is used to disperse for 1 to 5 minutes, and the viscosity is adjusted within a normal range to obtain an N-type TOPCon battery front grid line silver aluminum paste.
[0063] The present invention further provides an N-type TOPCon battery, wherein a plurality of grid lines are attached to the front side of the N-type TOPCon battery, and the grid lines are prepared from the above-mentioned silver-aluminum paste.
[0064] The present invention is described in detail below by way of examples.
[0065] Example 1
[0066] (1) Preparation of modified aluminum powder:
[0067] By mass, 3 parts of stearic acid are weighed as an organic modifier in a beaker or other container, and then 97 parts of butyl carbitol are weighed as a solvent and added to the beaker, placed in a magnetic stirrer, the temperature is controlled at 60 degrees, stirred at a speed of 400-800 rpm for 30 minutes, and then cooled, and then a certain amount of aluminum powder is weighed and added to the cooled beaker, and stirred at a speed of 300-500 rpm for 4 hours, and finally, excess solvent and modifier are filtered out with filter paper to obtain modified aluminum powder.
[0068] (2) Preparation of organic carrier:
[0069] Weigh 5 parts of organic polymer resin and 94 parts of organic solvent by mass, mix them, heat and disperse them on a disperser for 90 minutes, disperse and dissolve them, and then add 1 part of organic additive polyamide wax after cooling. Stir for 20 minutes to obtain a uniform organic carrier; wherein, by mass, the organic polymer resin includes 2 parts of EC and 1 part of acrylic acid, and the organic solvent includes 2 parts of butyl carbitol, 1 part of terpineol, and 1 part of tributyl citrate.
[0070] (3) Preparation of silicon glass powder:
[0071] a. Mix calcium oxide, boron oxide, zinc oxide and silicon oxide in a mass ratio of 10:60:15:25 and dry;
[0072] b. Put the dried glass powder raw material into a crucible, put the crucible into a high-temperature furnace for firing, raise the temperature to 1150°C and keep the temperature constant for 2 hours to obtain a glass melt;
[0073] c. Quench the glass melt with deionized water, remove the glass slag after cooling, and dry it;
[0074] d. Grind the glass slag using a ball mill to an average particle size of 2 μm;
[0075] e. Sieve and dry to obtain glass powder.
[0076] (4) Preparation of silver aluminum paste:
[0077] Modified aluminum powder, lead glass powder, silicon glass powder, organic carrier and silver powder were mixed in a mass ratio of 5:4:0.5:9:81.5, dispersed evenly using a disperser, and then ground with a three-roll grinder to a fineness of less than 6 microns to obtain silver-aluminum paste for the front grid line of an N-type TOPCon battery.
[0078] The silver-aluminum paste is screen-printed with 520 mesh on the front side of an N-type silicon wafer with a size of 182mm×182mm to form a positive grid line, with a main grid width of 0.4 microns and a fine grid width of 13 to 20 microns. The wafer is then put into a Despatch sintering furnace and sintered at a peak actual temperature of 700 to 760°C to obtain an N-type TOPCon battery.
[0079] The battery prepared in Example 1 was subjected to electrical property testing, and the results showed that the short-circuit current was 13.91 A, the open-circuit voltage was 710.2 mv, and the photoelectric conversion efficiency was 24.52%.
[0080] Example 2
[0081] The difference between Example 2 and Example 1 is that the organic modifier in step (1) is adjusted to a silane coupling agent.
[0082] The battery prepared in Example 2 was subjected to electrical property testing, and the results showed that the short-circuit current was 13.935 A, the open-circuit voltage was 711.2 mv, and the photoelectric conversion efficiency was 24.59%.
[0083] Example 3
[0084] The difference between Example 3 and Example 1 is that the organic modifier in step (1) is adjusted to oleic acid.
[0085] The battery prepared in Example 3 was subjected to electrical property testing, and the results showed that the short-circuit current was 13.941 A, the open-circuit voltage was 711.8 mv, and the photoelectric conversion efficiency was 24.635%.
[0086] Example 4
[0087] The difference between Example 4 and Example 1 is that the organic modifier in step (1) is adjusted to fatty acid.
[0088] The battery prepared in Example 4 was subjected to electrical property testing, and the results showed that the short-circuit current was 13.945 A, the open-circuit voltage was 712.1 mv, and the photoelectric conversion efficiency was 24.721%.
[0089] Example 5
[0090] The difference between Example 5 and Example 1 is that in step (1), the modifier is adjusted to stearic acid, silane coupling agent, oleic acid, and fatty acid, and the mass ratio of stearic acid, silane coupling agent, oleic acid, and fatty acid is 1:1:1:1.
[0091] The battery prepared in Example 5 was subjected to electrical property testing, and the results showed that the short-circuit current was 13.955 A, the open-circuit voltage was 713.1 mv, and the photoelectric conversion efficiency was 24.751%.
[0092] Example 6
[0093] The difference between Example 6 and Example 5 is that in step (4), the modified aluminum powder, lead glass powder, silicon glass powder, organic carrier and silver powder are mixed in a mass ratio of 1:10:0.1:15:73.9.
[0094] The battery prepared in Example 6 was subjected to electrical property testing, and the results showed that the short-circuit current was 13.943 A, the open-circuit voltage was 714.1 mv, and the photoelectric conversion efficiency was 24.782%.
[0095] Example 7
[0096] The difference between Example 7 and Example 5 is that in step (4), the modified aluminum powder, lead glass powder, silicon glass powder, organic carrier and silver powder are mixed in a mass ratio of 8:1:3:5:83.
[0097] The battery prepared in Example 7 was subjected to electrical property testing, and the results showed that the short-circuit current was 13.942A, the open-circuit voltage was 715.2mv, and the photoelectric conversion efficiency was 24.811%.
[0098] Example 8
[0099] The difference between Example 8 and Example 5 is that in step (4), the modified aluminum powder, lead glass powder, silicon glass powder, organic carrier and silver powder are mixed in a mass ratio of 8:10:0.1:11.9:70.
[0100] The battery prepared in Example 8 was subjected to electrical property testing, and the results showed that the short-circuit current was 13.952A, the open-circuit voltage was 715.4mv, and the photoelectric conversion efficiency was 24.832%.
[0101] Example 9
[0102] The difference between Example 9 and Example 5 is that in step (4), the modified aluminum powder, lead glass powder, silicon glass powder, organic carrier and silver powder are mixed in a mass ratio of 2:2:1:5:90.
[0103] The battery prepared in Example 9 was subjected to electrical property testing, and the results showed that the short-circuit current was 13.961A, the open-circuit voltage was 715.3mv, and the photoelectric conversion efficiency was 24.851%.
[0104] Comparative Example 1
[0105] The difference between Comparative Example 1 and Example 1 is that step (1) is omitted and the modified aluminum powder in step (4) is adjusted to aluminum powder.
[0106] The battery prepared in Comparative Example 1 was subjected to electrical property testing, and the results showed that the short-circuit current was 13.884A, the open-circuit voltage was 709.5mv, and the photoelectric conversion efficiency was 24.475%.
[0107] In summary, in the present embodiment, the provided silver-aluminum paste for the front grid line of an N-type TOPCon battery improves its surface oil absorption rate by coating the surface of the aluminum powder with an organic modifier, which not only reduces the interaction between the aluminum powders, but also makes the aluminum powder and the organic carrier in the slurry have better compatibility, and can be quickly and evenly dispersed into the organic or slurry, thereby reducing the agglomeration and fineness of the slurry, and ensuring smooth printing on a fine line and wide screen; at the same time, the organic is coated on the surface of the aluminum powder to reduce the surface oxidation of the aluminum powder, which is beneficial to the flow of aluminum liquid at a lower temperature during the sintering process, thereby improving the contact and efficiency, so that the silver-aluminum spikes on the silicon contact surface after sintering are small and numerous, thereby improving the VOC and contact performance of the battery, thereby solving the problem that the existing silver-aluminum paste for the front grid line of the N-type TOPCon battery is prone to broken grids and silver-aluminum spikes due to aluminum powder agglomeration during the printing process.
[0108] Although the preferred embodiments of the present invention have been described, those skilled in the art may make additional changes and modifications to these embodiments once they are aware of the basic creative concept. Therefore, the claims are intended to be interpreted as including the preferred embodiments and all changes and modifications that fall within the scope of the embodiments of the present invention.
[0109] The above is a detailed introduction to the silver-aluminum paste for the positive grid line of an N-type TOPCon battery and a battery provided by the present invention. Specific examples are used in this article to illustrate the principle and implementation mode of the present invention. The description of the above embodiments is only used to help understand the method of the present invention and its core idea. At the same time, for those skilled in the art, according to the idea of the present invention, there will be changes in the specific implementation mode and application scope. In summary, the content of this specification should not be understood as a limitation on the present invention.
Claims
1. A silver-aluminum paste for the front grid line of an N-type TOPCon battery, characterized in that: The components constituting the silver-aluminum paste include modified aluminum powder, silver powder, lead glass powder, silicon glass powder and an organic carrier. The modified aluminum powder is aluminum powder with an organic modifier coated on the surface.
2. The silver-aluminum paste according to claim 1, characterized in that: The mass fractions of the modified aluminum powder, silver powder, lead glass powder, silicon glass powder and organic carrier are 1-8%, 70-90%, 1-10%, 0.1-3% and 5-15% respectively.
3. The silver-aluminum paste according to claim 1, characterized in that: The organic modifier is one or more of stearic acid, silane coupling agent, oleic acid and fatty acid.
4. The silver-aluminum paste according to claim 1, characterized in that: The modified aluminum powder is micron spherical aluminum powder, and / or The D50 of the modified aluminum powder is 1 to 4 microns.
5. The silver-aluminum paste according to claim 1, characterized in that: The silver powder is micron-spherical silver powder, and / or The D50 of the silver powder is 0.5 to 3 microns.
6. The silver-aluminum paste according to claim 1, characterized in that: The lead glass powder is a lead-boron-zinc system glass powder, and / or The silicon glass powder is silicon-boron-zinc-calcium system glass powder.
7. The silver-aluminum paste according to claim 1, characterized in that: The organic carrier comprises 4 to 6 parts of an organic polymer resin, 93 to 95 parts of an organic solvent and 0.5 to 2 parts of an organic additive in parts by mass.
8. The silver-aluminum paste according to claim 7, characterized in that: The organic polymer resin includes one or more of EC, acrylic acid, and / or The organic solvent includes one or more of butyl carbitol, terpineol, tributyl citrate, and / or The organic additive is polyamide wax.
9. The silver-aluminum paste according to claim 1, characterized in that: The silicon glass powder comprises 5-20% by mass of calcium oxide, 10-60% by mass of boron oxide, 5-15% by mass of zinc oxide, and 10-30% by mass of silicon oxide.
10. An N-type TOPCon battery, characterized in that: A plurality of grid lines are attached to the front of the N-type TOPCon battery, and the grid lines are prepared by the silver-aluminum paste described in any one of claims 1 to 9.
Citation Information
Patent Citations
Lead-free environment-friendly electronic Ag / Al (silver / aluminum) paste and preparation method thereof
CN101950594A
Lead-free environment-friendly electronic aluminum paste and preparation method thereof
CN101984493A
Crystalline silicon solar cell silver-aluminum paste for low-temperature sintering, preparation method and application
CN114822909A